Control of the Microstructure in a Al5Co15Cr30Fe25Ni25 High Entropy Alloy through Thermo-Mechanical and Thermal Treatments - Pablo Pérez; Judit Medina; María Fernanda Vega; Gerardo Garcés; Paloma Adeva (Metals, 2023)
The effect of thermos-mechanical processing and thermal treatments on the microstructure of a single phase fcc-based Al5Co15Cr30Fe25Ni25 high entropy alloy is evaluated in this study. As-cast ingots of the high entropy alloy were thermo-mechanically processed following different routes involving forging, cold rolling, warm rolling or hot rolling. In addition, the microstructural evolution of highly deformed cold rolled sheets with the annealing temperature was analyzed. The data reveal that a high-volume fraction of the microstructure commences to recrystallize from 600 °C. In the absence of recrystallization, i.e., below 600 °C, the hardness of thermo-mechanically processed and annealed samples was very close. When recrystallization takes place, the thermo-mechanically treated alloys exhibit higher hardness than the annealed alloys because the recrystallized grains are strengthened by dislocations generated in further steps of the processing while the alloys in the annealed condition are free of dislocations. Maximum hardening is found for the alloy warm-rolled at 450 °C and the alloy cold-rolled plus annealing at 500 °C for 1 h. Diffusion of solute atoms to the core of dislocations, pinning its movement, accounts for the additional hardening.